2020
DOI: 10.1101/2020.09.25.312959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational design of genes encoding completely overlapping protein domains: Influence of genetic code and taxonomic rank

Abstract: Overlapping genes (OLGs) with long protein-coding overlapping sequences are often excluded by genome annotation programs, with the exception of virus genomes. A recent study used a novel algorithm to construct OLGs from arbitrary protein domain pairs and concluded that virus genes are best suited for creating OLGs, a result which fitted with common assumptions. However, improving sequence evaluation using Hidden Markov Models shows that the previous result is an artifact originating from dataset-database biase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…With increasing recognition that gene overlaps are functionally important and play vital roles within natural organisms, the construction of new overlapping genes has begun to be exploited in bioengineering. Theoretical work has previously shown that the genetic code is flexible enough to accommodate artificial overlap of protein domains 147 , 148 , and even artificial proteins 149 , often with the stated aim to protect the overlapping CDS from genetic drift 150 in similar ways to that found in viruses 71 , 75 , 151 .…”
Section: Overlapping Genes In Bioengineeringmentioning
confidence: 99%
“…With increasing recognition that gene overlaps are functionally important and play vital roles within natural organisms, the construction of new overlapping genes has begun to be exploited in bioengineering. Theoretical work has previously shown that the genetic code is flexible enough to accommodate artificial overlap of protein domains 147 , 148 , and even artificial proteins 149 , often with the stated aim to protect the overlapping CDS from genetic drift 150 in similar ways to that found in viruses 71 , 75 , 151 .…”
Section: Overlapping Genes In Bioengineeringmentioning
confidence: 99%
“…Amino acid coding with respect to complementary protein constructs, mutation, and frameshifts have been studied by many authors, including Arques and Michel [41,42], Bartonek et al [43], McGuire and Holmes [21], Štambuk [44,45], Wichmann et al [46,47], and Youvan et al [48][49][50].…”
Section: Amino Acid Coding Complementarity and Frameshiftsmentioning
confidence: 99%